Just Like a Woman? Effects of Gender-Biased Perceptions of Friendship Network Brokerage on Attributions and Performance - Brands, Raina A.; Kilduff, Martin (Organization Science, 2014)
Do women face bias in the social realm in which they are purported to excel? Across two different studies (one organizational and one comprising MBA teams), we examined whether the friendship networks around women tend to be systematically misperceived and whether there were effects of these misperceptions on the women themselves and their teammates. Thus, we investigated the possibility (hitherto neglected in the network literature) that biases in friendship networks are triggered not just by the complexity of social relationships but also by the gender of those being perceived. Study 1 showed that, after controlling for actual network positions, men, relative to women, were perceived to occupy agentic brokerage roles in the friendship network—those roles involving less constraint and higher betweenness and outdegree centrality. Study 2 showed that if a team member misperceived a woman to occupy such roles, the woman was seen as competent but not warm. Furthermore, to the extent that gender stereotypes were endorsed by many individuals in the team, women performed worse on their individual tasks. But teams in which members fell back on well-rehearsed perceptions of gender roles (men rather than women misperceived as brokers) performed better than teams in which members tended toward misperceiving women occupying agentic brokerage roles. Taken together, these results contribute to unlocking the mechanisms by which social networks affect women’s progress in organizations.